1998
DOI: 10.1084/jem.188.10.1967
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Pulmonary Eosinophilia Is Mediated by a Specific Amino Acid Sequence of the Attachment (G) Protein of Respiratory Syncytial Virus

Abstract: We analyzed the immune responses evoked by a series of overlapping peptides to better understand the molecular basis for respiratory syncytial virus (RSV) G protein–induced eosinophilia in BALB/c mice. In vitro stimulation of spleen cells from natural G protein–primed mice showed dominant proliferative and cytokine (interferon [IFN]-γ and interleukin [IL]-5) responses to a peptide encompassing amino acids 184–198. Mice vaccinated with peptide 184– 198 conjugated to keyhole limpet hemocyanin showed significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 28 publications
6
98
0
5
Order By: Relevance
“…However, the complete absence of G protein severely restricted replication in vivo and thus limited the potential of the rRSV strain as a vaccine. Alternatively, efficacious immunity was observed (47) following immunization of BALB/c mice with vaccinia virusexpressed G protein in which the region shown to be responsible for eosinophilia was altered by a frameshift (50,55). Following challenge with the Long strain of RSV, eosinophilia was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complete absence of G protein severely restricted replication in vivo and thus limited the potential of the rRSV strain as a vaccine. Alternatively, efficacious immunity was observed (47) following immunization of BALB/c mice with vaccinia virusexpressed G protein in which the region shown to be responsible for eosinophilia was altered by a frameshift (50,55). Following challenge with the Long strain of RSV, eosinophilia was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analysis of several RSV G protein frameshift mutants has revealed that a particular region spanning aa 193-205 of the G protein is required to induce pulmonary eosinophilia, a process that is dependent on CD4 ϩ T cell recognition of G (22). Furthermore, a separate study established that immunization of BALB/c mice with a peptide derived from aa 184 -198 of the G protein led to the development of pulmonary eosinophilia after intranasal infection with RSV (23). Finally, recent studies from our laboratory have demonstrated that both Th1 and Th2 CD4 ϩ T cells are elicited to a single RSV G-derived peptide encompassing aa 183-197 (24).…”
Section: D4mentioning
confidence: 99%
“…It is now proposed that the formalin inactivated RSV vaccine elicited little neutralizing antibody, explaining the lack of protection. Moreover, in subsequent research studies, animals inoculated with the formalin-inactivated vaccine and challenged with RSV experienced severe lung inflammatory responses characterized by a skewed CD4+ T-cell response (in the absence of neutralizing antibodies) and the influx of eosinophils in the lung [5][6][7][8][9][10][11]. The importance of B-cell responses to protection has been demonstrated by a number of passive protection studies using RSVneutralizing immune globulin and humanized monoclonal antibodies [1;12-14].…”
Section: Introductionmentioning
confidence: 99%